RENCANA PENGELOLAAN GREEN BUILDING DENGAN PENDEKATAN BUILDING ENVIRONMENT MANAGEMENT (BEM) - Regina Regina; Liong Ju Tjung; Priyendiswara A.B. Priyendiswara (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The concept of green building is now increasingly being applied in Indonesia, especially DKI Jakarta due to the increasing prevalence of global warming. Adapting to climate change and the increasing number of tall buildings in Indonesia, the GBCI (Green Building Council Indonesia) concluded that the biggest cause of energy use was due to the use of the building sector of around 48%, while the other 27% was in the transportation sector, then 25% in the industrial sector. GBCI applies certification in the form of "Greenship" as an assessment tool for buildings that are rated as Green Buildings. "Greenship" is prepared by GBCI by considering the conditions, nature, rules and standards that apply in Indonesia. The main focus of Green Building is energy efficiency, but what distinguishes "Greenship" from other rating tools are "Greenship" has a BEM category that focuses on managing the waste produced by buildings. The rating tool "Greenship" in Indonesia is quite balanced because in addition to focusing on energy efficiency, "Greenship" also pays attention to the comfort elements of its occupants, namely the Building Environmental Management category (BEM) where the comfort of buildings is one of the factors in the success of green buildings. In order for green building to be managed optimally, the author compiled a study of the criteria for BEM (Building Environment Management), with recommendations for waste and fit-out management in one of Green Building in Jakarta, South Quarter with a BEM achievement of 77%. The author composes the recommended budgetary costs for evaluating waste sorting and training, the author also conducted tenant perceptions surveys with cross tabulation and compare means method with the results that 77% of respondents agreed with the planning of sorting waste and providing training for residents of the building at the Green Building.the result that 77% of respondents agreed with planning waste sorting and providing training to building occupants in the Green Building.AbstrakKonsep bangunan hijau saat ini semakin banyak diimplementasikan di Indonesia khususnya DKI Jakarta karena semakin maraknya pemanasan global. Beradaptasi dengan perubahan iklim dan semakin banyaknya bangunan tinggi di Indonesia, GBCI (Green Building Council Indonesia) menyimpulkan bahwa penyebab terbesar dari penggunaan energi yaitu karena penggunaan pada sektor bangunan sekitar 48%, sedangkan 27% lainnya sektor transportasi, lalu 25% sektor industri. GBCI menerapkan sertifikasi berupa “Greenship” sebagaii alat penilai/penentu untuk sebuah bangunan dinilai sebagai Green Building. “Greenship” dipersiapkan oleh GBCI dengan mempertimbangkan kondisi, karakter alam serta peraturan dan standard yang berlaku di Indonesia. Fokus utama dari Green Building adalah efisiensi energi, namun yang membedakan “Greenship” dengan rating tools lainnya yaitu “Greenship” mempunyai kategori BEM yang berfokus kepada pengelolaan sampah yang dihasilkan oleh gedung. Rating tools berupa “Greenship” di Indonesia cukup seimbang karena selain berfokus pada efisiensi energi, “Greenship” juga memperhatikan unsur kenyamanan penghuninya yaitu dengan adanya kategori Manajemen Lingkungan Bangunan (BEM) dimana kenyamanan penghuni bangunan merupakan salah satu faktor keberhasilan dari green building. Agar suatu green building dapat dikelola secara maksimal, penulis menyusun penelitian pada kriteria BEM (Building Environment Management), dengan rekomendasi untuk pengelolaan sampah dan fit-out di salah satu Green Building di Jakarta yaitu South Quarter dengan pencapaian BEM sebesar 77%. Penulis menyusun biaya anggaran yang disarankan untuk evaluasi pemilahan sampah dan training, penulis juga melakukan survei persepsi tenant dengan metode tabulasi silang dan perbandingan nilai tengah dengan hasil bahwa 77% responden setuju dengan perencanaan pemilahan sampah dan pengadaan training untuk penghuni gedung di Green Building.